Pengaruh Pengaruh Model Pembelajaran Flipped Classroom terhadap Hasil Belajar Pola Bilangan Peserta Didik SMPN 3 Kotabumi - Asmita Ningsih; Venty Meilasari; Darwanto (Eksponen, 2022)
Abstract: The purpose of this study was to determine whether or not there was an effect of the flipped classroom learning model on the learning outcomes of the number pattern of students in class Vlll SMP Negeri 3 Kotabumi. The research method used is experimental research, the design is quasi-experimental. The population in this study was class VIII SMP N 3 Kotabumi in the academic year 2022/2023 and the samples in this study were class Vlll B and Class Vlll C. The sampling technique used cluster sampling. The data collection instrument used multiple-choice test questions. The data analysis technique used n gain test, t-test and prerequisite test. The results of the research that have been carried out, obtained the t-test at the value of n gain, that is, it is rejected. So it can be concluded that there is an effect of the application of the flipped classroom learning model on the learning outcomes of class VIII students of SMP Negeri 3 Kotabumi's number pattern. Keywords: flipped classroom learning model, learning outcomes, number patterns Abstrak: Tujuan pada penelitian ini untuk mengetahui ada atau tidak pengaruh model pembelajaran flipped classroom terhadap hasil belajar pola bilangan peserta didik kelas Vlll SMP Negeri 3 Kotabumi. Metode penelitian yang digunakan penelitian eksperimen, desainnya menggunakan quasi experimental.. Populasi pada penelitian ini peserta didik kelas Vlll SMP N 3 Kotabumi tahun ajaran 2022/2023 dan sampel pada penelitian ini yaitu kelas Vlll B dan Vlll C. Teknik sampling menggunakan cluster sampling. Instrumen pengumpulan data menggunakan soal tes berbentuk pilihan ganda. Teknik analisis data menggunakan uji n gain, uji-t dan uji prasyarat. Hasil penelitian yang telah dilakukan, diperoleh uji-t pada nilai n gain yaitu maka ditolak. Sehingga dapat disimpulkan ada pengaruh penerapan model pembelajaran flipped classroom terhadap hasil belajar pola bilangan peserta didik kelas VIII SMP Negeri 3 Kotabumi. Kata Kunci : Model pembelajaran flipped classroom, hasil belajar, pola bilangan